Data Sharing Defined—Really! - Handler, Ivan (Computer (00189162), 2018)
A clear and comprehensive policy framework is needed to make data sharing more useful, robust, and efficient. Based on decades of experience as a CIO in the healthcare sector, the author recommends ways to address various existing privacy, reliability, interoperability, security, and trust challenges.